Interpersonal Process-Oriented Group Psychotherapy with Offender Populations - Morgan, Robert D. (International journal of offender therapy and comparative criminology, 2002)
This article discusses the application of interpersonal process-oriented group psychotherapy to offender populations. Group psychotherapy with offenders presents problems not encountered with other populations; thus, applying the group method requires special considerations. The particular focus of this article is on the relevance of therapeutic factors in group work with offenders, group process as it applies to work with offenders, and work with difficult clients